2020
DOI: 10.3389/fpsyg.2020.584857
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Behaviors Through Institutional Support in British Higher Educational Institutions: Focusing on Employees for Sustainable Technological Change

Abstract: Technology permeates all walks of life. It has emerged as a global facilitator to improve learning and training, alleviating the temporal and spatial limitations of traditional learning systems. It is imperative to identify enablers or inhibitors of technology adoption by employees for sustainable change in education management systems. Using the theoretical lens of organizational support theory, this paper studies effect of institutional support on education management information systems (EMIS) use along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 103 publications
(163 reference statements)
3
10
0
Order By: Relevance
“…Given said interaction of contextual, organizational and personal factors, a permanent organizational diagnosis is required ( Mercader & Gairín, 2020 ). On the other hand, our results agree with those obtained by Zhao et al (2020) , who state the value of training to stimulate EMIS usage by employees.…”
Section: Discussionsupporting
confidence: 92%
“…Given said interaction of contextual, organizational and personal factors, a permanent organizational diagnosis is required ( Mercader & Gairín, 2020 ). On the other hand, our results agree with those obtained by Zhao et al (2020) , who state the value of training to stimulate EMIS usage by employees.…”
Section: Discussionsupporting
confidence: 92%
“…However, the variable of actual use can be replaced by the WTP value (Arogundade et al, 2016). Consistent with the findings of the original TAM (Zhao et al, 2020), the results of prior studies confirmed that perceived usefulness and perceived ease of use are significant determinants of payment intention. Besides, payment intention has a significant effect on the WTP value (Wicker et al, 2016).…”
Section: Previous Study Of the Willingness To Paysupporting
confidence: 80%
“…It could be more complicated for users to watch sports events by streaming media than by traditional TV (Alalwan et al, 2018;Yang and Lee, 2018). A number of previous studies showed that perceived ease of use significantly and positively affected users' intentions (Alalwan et al, 2016;Zhao et al, 2020). Hence, the following hypothesis is proposed: H2.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…First, it facilitates the analysis of multifaceted models comprising several constructs, indicators, and relationships (Ringle et al, 2018 ). Second, due to its dominance over other techniques while analysing mediation; third, it is particularly appropriate for prediction‐oriented studies (Zhao, Ahmed, Iqbal, et al, 2020 ), for instance, nurses' burnout. Fourth, it is equipped with the latest statistical tools, including confidence intervals for hypothesis testing, effect size to know the relative contribution of predictor constructs, graphs for moderation analysis, and heterotrait–monotrait (HTMT) ratio for discriminant validity.…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…Lastly, comparatively, it offers better statistical power. PLS‐PM comprises a two‐stage approach for analysis (Hair et al, 2020 ), and for these reasons, its use has increased over the years in management research (Zhao, Ahmed, & Faraz, 2020 ; Zhao, Ahmed, Iqbal, et al, 2020 ) in recent years.…”
Section: Analysis and Findingsmentioning
confidence: 99%